'Distilling More than 2, 000 Years of History into 161, 000 Square Feet of Display Space': Limiting Britishness and the Failure to Create a Museum of British History. Issue 2 (14th September 2016) - CARTER, TOM; ROBERTSON, IAIN
Abstract: National museums both mediate and inculcate official and formal versions of national culture and by this means make and maintain national identity. Three times in the course of the twentieth century, various groups have attempted, and failed, to establish a national museum, identified variously as British or English. This paper explores just one of those attempts: the Museum of British History Project, first proposed in 1996 and finally killed off in 2008. The focus here is, therefore, on failure and on the role of the conflation of Britishness and Englishness in that failure as well as the nature of British identity construction more generally. All three attempts to create a national museum placed the rural idyll at the heart of the project. In the course of a detailed investigation of the Museum of British History project, this paper will pay particular attention to the proposed designs for a 'British Landscape Gallery' and the project's hegemonic, ruralised and Anglocentric perspectives. The gallery was the principal way in which established constructs of England and Englishness became conflated in the museum with Britain and Britishness and served to perpetuate the dominance of the 'rural idyll' in hegemonic manifestations of the nation. But the project remained stillborn in the face of the new museology: a failure which undoubtedly demonstrates the limits to the cultural power of the rural idyll.